Optimising preoperative diagnosis in phyllodes tumour of the breast. Issue 5 (6th February 2006) - Jacklin, R K; Ridgway, P F; Ziprin, P; Healy, V; Hadjiminas, D; Darzi, A
Abstract : The role of the pathologist in the preoperative diagnosis of phyllodes tumours of the breast is critical to appropriate surgical planning. However, reliable differentiation of phyllodes tumour from cellular fibroadenoma remains difficult. Preoperative diagnostic accuracy allows correct surgical treatment, avoiding the pitfalls of reoperation because of inadequate excision, or surgical overtreatment. Specific clinical indices may arouse diagnostic suspicion but are unreliable for confirmation, as with current imaging modes. Fine needle aspiration cytology has a high false negative rate. Few studies have evaluated the role of core needle biopsy, but it may prove a useful adjunct. Both diagnostic and prognostic information may in future be gained from application of immunohistochemical and other techniques assessing the expression of proliferative markers including p53, Ki-67, and others.